2023
DOI: 10.3390/app13148171
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Zoning of the Baikal Basin Based on the Results of Chemical Analysis of the Composition of Atmospheric Precipitation Accumulated in the Snow Cover

Abstract: This research used the geostatistical analysis of snow cover samples taken in 2017–2022 in the Baikal basin. Groups of snow cover pollution sources were identified by the method of empirical Bayesian kriging (ArcMap software) and mathematical data processing. The studied area was divided into fourteen districts. Geovisualization of marker substances accumulated in the snow cover allowed for the zoning of the studied area according to the degree of anthropogenic load. It was revealed that the atmospheric pollut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
(71 reference statements)
0
0
0
Order By: Relevance
“…Based on the monitoring data for the southern basin of Lake Baikal, Obolkinet al [31] found that emissions from large thermal power plants reach heights of several hundred meters in the atmosphere and are carried by air masses over a distance of hundreds of kilometers. Likewise, Molozhnikova et al [32] analyzed the snow-pollution levels for the same region and found that emissions from the larger cities were transferred to distances of tens of kilometers by prevailing winds. The cross-regional transport of air pollutants by air flows from cities to rural backgrounds and even between cities contributes significantly to local air quality [33][34][35][36].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the monitoring data for the southern basin of Lake Baikal, Obolkinet al [31] found that emissions from large thermal power plants reach heights of several hundred meters in the atmosphere and are carried by air masses over a distance of hundreds of kilometers. Likewise, Molozhnikova et al [32] analyzed the snow-pollution levels for the same region and found that emissions from the larger cities were transferred to distances of tens of kilometers by prevailing winds. The cross-regional transport of air pollutants by air flows from cities to rural backgrounds and even between cities contributes significantly to local air quality [33][34][35][36].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The AE value of the ZS site is higher than that of the NJ site. This may be caused by the frequent industrial activities and traffic activities in Nanjing area [45][46][47]. The AE peak of the NJ site appeared in the afternoon.…”
Section: Diurnal and Weekly Variations Of Aerosols No2 And Hchomentioning
confidence: 99%